2018
DOI: 10.3390/ijms19071945
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of CARK1 or RCAR11 Driven by Synthetic Promoters Increases Drought Tolerance in Arabidopsis thaliana

Abstract: Drought stress hinders plant growth and development, and abscisic acid (ABA) stimulates plants to respond to drought. Here, to increase plant tolerance to drought, we designed three synthetic promoters (Ap, Dp, ANDp) to determine transcription activity and drought stress resistance in plants resulting from combinations of (1) synthetic promoters and (2) the functional genes CARK1 (cytosolic ABA receptor kinase 1) and RCAR11 (regulatory components of ABA receptor 11). Transient expression of eGFP and the dual-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…For the drought stress tolerance assay, two-week old hd2 mutant or HD2-OE plants in drought-treated groups were withheld from watering for 11 and 13 days, respectively ( Ge et al., 2018 ). After the drought stress period, plants were rewatered for two days to allow them to recover.…”
Section: Methodsmentioning
confidence: 99%
“…For the drought stress tolerance assay, two-week old hd2 mutant or HD2-OE plants in drought-treated groups were withheld from watering for 11 and 13 days, respectively ( Ge et al., 2018 ). After the drought stress period, plants were rewatered for two days to allow them to recover.…”
Section: Methodsmentioning
confidence: 99%
“…Wu et al reported that the spatial pattern of abscisic acid (ABA) mediated transcriptional regulation by evaluating an 'abscisic acid responsive element' (ABRE) in root tissues [80]. The interaction of the synthetic promoter in association with functional genes responsible for cytosolic ABA, receptor kinase 1 (CARK1), and regulatory components of ABA receptor 11 (RCAR11) lead to drought stress tolerance [81].…”
Section: Development Of Hormonal-responsive Synthetic Promotersmentioning
confidence: 99%
“…In particular, EKCM showed a 1.29-fold increase in GUS activity in different tissues of transgenic A. thaliana under dehydration conditions (Hou et al, 2012). Synthetic promoters Ap, Dp, and ANDp were also designed to provide drought resistance in plants (Ge et al, 2018). The combination of functional genes for cytosolic abscisic acid (ABA) receptor kinase 1 ( CARK1 ) and regulatory components of ABA receptor 11 ( RCAR11 ) with synthetic promoters resulted in drought stress tolerance.…”
Section: Functional Characteristics Of the Promoters And Transgenic Pmentioning
confidence: 99%
“…The combination of functional genes for cytosolic abscisic acid (ABA) receptor kinase 1 ( CARK1 ) and regulatory components of ABA receptor 11 ( RCAR11 ) with synthetic promoters resulted in drought stress tolerance. It was also reported that exogenous ABA or co-transformation with the effector dehydration-responsive element binding protein 2A (DREB2A) induced the activity of the synthetic promoters (Ge et al, 2018). They concluded that a combination of synthetic promoters and functional genes ( Dp.RCAR11 - Ap.CARK1 and ANDp.CARK1 ) can be used to generate drought stress resistance in different plants.…”
Section: Functional Characteristics Of the Promoters And Transgenic Pmentioning
confidence: 99%